Role of Small Business in Further Development of Textile and Knitting Industry - Maksudov Abdusalam Nuralievich (Research Parks Publishing LLC, 2023)
Today's indicators of the textile industry of New Uzbekistan, foreign investments attracted to the industry, modernization of the industry, tasks defined in the creation of promising types of ready-made fabrics in the country, and the main directions of the development of the industry are dedicated. The article also uses methods such as statistical analysis, empirical evaluation, systematic and factor analysis, economic-mathematical modeling, statistical grouping, expert evaluation, systematic approach, situational approach, and SWOT analysis. Proposals and conclusions on the development of the textile and sewing-knitting industry are given.